THE PHENOMENON OF BOLSHEVISM IN THE EARLY SOVIET ERA: DOCTRINE, POLITICAL PRACTICE, EVOLUTIONARY RELATIONS - HULA, Ruslan; PEREDERII, Iryna (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
The role and place of the Bolshevism phenomenon in the development of the political process of the 1920s are analyzed. The meaning of the concept of «Bolshevism» is revealed and the author’s vision of its components in the theory and socio-political practice of the «conservative revolution» is offered. The peculiarities of the functioning of Bolshevism in the paradigm of the «conservative revolution» are considered. The debate researchers about the nature of Stalinism is also relevant in our time. Most scholars believe that Stalinism and Bolshevism are ontological twins. But Bolshevism is a socio-political phenomenon that is much broader than Leninism. Bolshevism denied traditional values – patriotism, family, religion. Bolshevism laid the foundations of the Stalinist model of state administration. Bolshevism is a philosophical doctrine and socio-political practice based on the glorifcation of the role of the proletariat, the denial of the religious and spiritual foundations of society, the unifcation of economic life against the background of pseudo-socialist rhetoric. The main features of Bolshevism are: the apology of violence and terror, social selection; class-internationalist orthodoxy; social utopianism – «the construction of Paradise on the Earth» based on the doctrine of K. Marx and messianism – a claim to the only correct recipe for «happiness of all mankind»; a new type of proletarian «democracy»; aggressive denial of religion. Bolshevism arose on the basis of the Leninist vision of Marxism. But the modernism of Western social philosophy entered into systemic contradictions with the realities of post-imperial Russia. The construction of a new type of society was based on the principles of total state terror in a bloody civil war. Stalinism left in its foundation the rudiments of monoideologism, antidemocratism, punitive-terrorist practice, and the sacralization of the socialist teachings of Bolshevism. But the «leader of the nations» in the early 1930s. Returned to the utilitarian-pragmatic use of those constants of traditional worldview dogma that allow us to interpret Stalinism as an organic component of the «conservative revolution» of the 1920s and 1930s with appropriate correction and correlation.